Development of Information System for Enhancing the Competency in the Competitiveness of Small and Medium Enterprises in Northern Region of Thailand - Pongwiritthon, Ratthanan (WMS Journal of Management, 2018)
The purpose of this research aims to develop the information system in order to give the advice, suggestion or training to enhance the productivity of “The loan for productivity development project”. The assessment of the potential of the entrepreneurs will enhance the competency in the competitiveness of Small and Medium Enterprises in the northern region of Thailand according to the concept of SHINDAN. The system is developed by the database management system of Microsoft SQL server as well as ASP.NET server script and then tries on the trail usage. The data were collected from 350 entrepreneurs in the northern region of Thailand by the information system by the expert in coaching evaluation. The information was then used as the primary consultative to the improvement in each issue and transfers the knowledge to the entrepreneurs to be able to use the system on their own. The result shows that the satisfaction of the entrepreneurs towards the information system in overall at the highest level (x̅ = 4.89, S.D. = 0.85). In terms of each aspect, the highest satisfaction level is on the utilization aspect (x̅ = 4.65, S.D. = 0.73), the efficiency system aspect (x̅ = 4.92, S.D. = 0.32), and the possibility aspect (x̅ = 4.83, S.D. = 1.52). To enhance the competitiveness in the business, it is necessary to focus on: 1. There should be public relations about the system and prepare the information in order to assess and able to solve the problem in time. 2. Provide the training in solving the problems of the entrepreneurs from the report and use the result of the information to apply by providing effective technical assistance from both government and private agencies. 3. The entrepreneur should learn to apply to use the innovation and technologies to maximize the efficiency of the available limited resources.